Meningkatkan Hasil Belajar Bahasa Indonesia Menggunakan Model Problem Based Learning, Number Head Together Dan Make A Match Pada Siswa Sekolah Dasar - Norlena Adha; Susilawaty . (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The lack of student learning outcomes in Indonesian language learning is the core of the problem being studied. The underlying key is because learning is one-way and the incompatibility of the models or methods implied to trigger students to be less active in learning. Efforts that can be realized are by implementing the Problem Based Learning, Number Head Together and Make A Match learning models. Describing the improvement of Indonesian language learning outcomes, especially in the aspect of reading comprehension in exploring important information from narrative texts, implementing the Problem Based Learning, Number Head Together and Make A Match Models for Class V Students of SDN Duyun Baru, Bintang Ara District, Tabalong Regency, is the objective underlying the research. This Classroom Action Research (CAR) embraced 20 Class V students who were carried out on 3 occasions to explore qualitative and quantitative data. The study interpreted the activities of the third opportunity teacher as being included in the 100% category. The learning outcomes of the third opportunity reached 84, including in the category of achieving the KKM value > 70. The results of the third meeting were included in the complete category.